A new species of the genus Sovia (Lepidoptera: Hesperiidae) from Qinling-Daba Mountains of China - Xue, Guo-Xi; Li, Meng; Nan, Wen-Hao; Jia, Xing-Long; Huang, Si-Yao; Sun, Hao; Li, Xiao-Juan (Zootaxa, 2015)
In this paper, a new species Sovia lii spec. nov. is described from Qinling-Daba Mountains in S. Gansu province and S. Shaanxi province, W. China. Variability of wing pattern, differences with its similar congeners and some biological information of this new taxon are introduced. External variability of Sovia lucasii, which is discovered from Shaanxi for the first time and is sympatric with the new species there, is illustrated and discussed. A brief analysis of the distributional pattern of the genus Sovia is provided. A key to the genus is given.